Socio-egocentrism theory, research and practice - Peters, James S. (Internat. Scholars Publ., 1997)
The book is a compendium of thirty years of research and practice in self and social perception - Socio-Egocentrism - a relationship between the self and other people. This important research began with Dr. Peters' pioneering studies of juvenile offenders at Purdue University. Based on his studies of juvenile delinquency, Dr. Peters has developed his theories involving other clinical groups. The author posits a measurable scale of cognitive and personal changes to describe the progress that can be made as emotional improvement occurs in a patient.